Evaluation of Chrisofix® Chest Orthosis Application in Patients with Traumatic Rib Fractures (Bangladesh Journal of Medical Science, 2024)
Background: The Chrisofix® Chest Orthosis is an effective and easy to use device for the treatment of rib fractures. It is used as a supportive treatment to reduce the pain levels and complication risks of the patients.Methods: Patients hospitalized with the diagnosis of rib fractures in the Thoracic Surgery Service of a university hospital were retrospectively scanned in an online computer program between October 2018 and October 2021. The study sample consisted of patients with the treatment (30) and control (30) groups.Results: Visual Analog Scale and incidence of atelectasis of the patients in the experimental group (The Chrisofix® Chest Orthosis) is statistically significantly lower than the control group (P < 0.05). In both the experimental and control groups, no statistically significant difference was found between the variables of patient’s demographic and clinical characteristics (p > 0.05).Conclusions: In the study, with the use of The Chrisofix® Chest Orthosis, a significant decrease was observed in the Visual Analog Scale and the incidence of atelectasis.Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 83-88